Union of the Comoros : Enhanced Initiative for Heavily Indebted Poor Countries: Completion Point Document and Multilateral Debt Relief Initiative. (IMF Staff Country Reports; Country Report ;, 2013)
In June 2010, the International Development Association (IDA) and the IMF agreed that Comoros had met the requirements for reaching the decision point under the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative. As a result of the debt reconciliation exercise for the completion point, the present value of eligible external debt at end-2009 has been revised upward. Full delivery of HIPC assistance together with additional bilateral assistance beyond HIPC and Multilateral Debt Relief Initiative (MDRI) debt relief at the completion point would reduce Comoros' external debt burden significantly.